THE RELATIONSHIP BETWEEN CENTRAL AND LOCAL AUTHORITIES IN THE GOVERNANCE MECHANISM OF THE NORTHERN FRONTIER UNDER THE LÝ DYNASTY (1009-1226) - Thu Hien, Nguyen; Thi Thanh Hien, La; Phuong Mai, Luong (HNUE Journal of Science: Journal of Social Sciences, 2026)
This paper examines the relationship between central and local authorities in the governance of the northern frontier under the Lý Dynasty (1009-1226). It focuses on the interaction between state policies and the specific characteristics of the frontier region, thereby clarifying the administrative mechanisms applied in this area. Based on premodern Vietnamese historical sources and an analysis of major historical events, the study elucidates two key elements: the rule-based governance and local autonomy, as well as their roles in the management of the frontier region. The findings show that the governance of the northern frontier under the Lý Dynasty was carried out through a combination of strengthening central authority by means of law and recognizing certain forms of autonomy among local communities and ethnic minority groups. The relationship between the central government and local forces was flexible rather than confrontational, varying between submission, conflict, and cooperation depending on the socio-political context. This paper thus contributes to clarifying the characteristics of frontier governance under the Lý Dynasty, which aimed to maintain social stability, ensure border security, and reinforce central authority in the historical context of medieval Đại Việt.